Analisis Faktor yang Mempengaruhi Kemandirian Belajar Siswa Semasa Pandemi Covid-19 - Shara Dwi Amiza; Rita Syofyan (Universitas Negeri Padang, 2023)
This study aims to analyze the factors that influence student learning independence during the Covid-19 pandemic in students of SMK Negeri 1 Padang Panjang for the 2020/2021 Academic Year. This type of research is a quantitative descriptive study using a purposive sampling technique. The population in this study were all students of SMK Negeri 1 Padang Panjang, amounting to 895 people. The sample used was 100 respondents. The type of data in this study is primary data with data collection techniques using questionnaires. The data has been collected and analyzed using descriptive analysis and factor analysis based on 3 existing factors. The results of this study indicate that there are 6 factors that have been confirmed to affect student learning independence during the Covid-19 pandemic in SMK Negeri 1 Padang Panjang students, namely family environmental factors, interest factors, and relationship/communication factors, creativity factors, motivational factors, and socio-economic factors. The most dominant factor influencing student learning independence during the Covid-19 pandemic is the family environment.